SERUM TESTOSTERONE LEVELS IN YOUNG MALE PATIENTS WITH MAJOR DEPRESSION - Yousafzai, Aziz ur Rehman; Yousuf, Muhammad; Jan, Muhammad; Badar, Ahmed (Journal of Ayub Medical College Abbottabad, 2000)
Background: Testosterone affects neurobehavioral functions in men. It has positive effects on the mood. The available studies suggest that some depressed older men may have state-dependent low testosterone levels and that some depressed men may improve with androgen treatment. This study was done to look for relationship of testosterone level with major depression in young patients. The daytime testosterone level and nighttime testosterone level in the subjects was also compared. Methods: 25 young patients admitted in psychiatry7 unit of Ayub Teaching Hospital in the age range 25-35 years were randomly selected for the study. It was ascertained that none of the subjects was sexually abnormal before the onset of disease. Daytime sample was taken at 12 noon while the nighttime sample at 12 midnights. The testosterone level was done by radioimmunoassay. The results were compared with matching controls. Results: The daytime and nighttime means were compared between the controls and subjects. Both the values were significantly lower in the depressed subjects. The value of nighttime testosterone was significantly more than the daytime testosterone in the depressed subjects. Conclusion: Testosterone level is significantly decreased in young patients with major depression.